PENGUATAN GENERASI MUDA BERBASIS KOMUNITAS (IMPLEMENTASI PROGRAM DI PANTI ASUHAN KAFALATUL YATAMA SEMARANG) - Misbah Zulfa Elizabeth (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
The youth is the holder estafeta human struggle and development. But in reality , not all young people have the opportunity to forge themselves in order to prepare their individual role in their family since his parents died or because of other calamity. Life in the orphanage then to be an option . With a participatory approach this community engagement program aims to find out what the needs of youth in the orphanage , how to plan and implement communitybased programs, and what the results obtained. Results of the program are: (1) there are motivation to be independent, productive, and responsible, (2) the importance of planting the propagation of Islam as well as the awareness of the importance of public speaking to convey the values of Islam, (3) Entrepreneurship is a subject preparation assistance to have creative and productive life and is a determinant aspect of community empowerment, and (4) IT training is a very important training for debriefing subjects beneficiaries